Entrepreneurial Resilience, Digital Literacy, Business Adaptability, and MSME Performance in Semi-Rural Indonesia - Nila Rahma Ningsih; Muh. Fahrurrozi; Susilawati Susilawati (Sumber Belajar Sejahtera, 2026)
Purpose - Micro, small, and medium enterprises (MSMEs) are central to employment creation, local income generation, and regional economic resilience in Indonesia. Yet semi-rural MSMEs often operate under market volatility, resource constraints, and uneven digital readiness. This study examines the effects of entrepreneurial resilience, digital literacy, and business adaptability on MSME performance in Sikur District, East Lombok Regency. Design/methodology/approach A quantitative survey design was used. The population comprised 753 MSME owners, and 100 respondents were selected using the Slovin formula and simple random sampling. Data were collected using a structured five-point Likert-scale questionnaire and analysed with validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-test, and coefficient of determination using IBM SPSS Statistics. Findings Entrepreneurial resilience has a positive and significant effect on MSME performance (B = 0.168; standardized beta = 0.254; p = 0.003). Business adaptability is the strongest predictor (B = 0.440; standardized beta = 0.619; p < 0.001). Digital literacy has a positive but non-significant effect (B = 0.035; standardized beta = 0.052; p = 0.550). Simultaneously, the three predictors significantly explain MSME performance, F(3, 96) = 108.042, p < 0.001, with R2 = 0.771. Originality/value - The study extends MSME performance research by integrating entrepreneurial resilience, digital literacy, and business adaptability in a semi-rural Indonesian setting. The findings suggest that digital literacy alone may not immediately improve performance unless it is translated into concrete digital practices, while adaptability and resilience remain decisive capabilities for sustaining MSME competitiveness.